IMPROVING READING COMPREHENSION ON DESCRIPTIVE TEXT BY USING SEMANTIC MAPPING - Suciati, Dewi; ., Regina; Wijaya, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The aim of this research is to improve students’ reading comprehension, especially in getting main idea, supporting detail and vocabulary aspect. This research was conducted to the first grade students of SMK PGRI Pontianak in academic year 2014/2015. In this research, the subject is Teknik Audio Video class that consists of 20 students. The researcher conducted a classroom action research in her research and acted as the teacher during the research period. The data were collected by using direct and measurement technique. The tools of data collecting were observation checklist, field note, and test. Semantic mapping was used as the technique in this research which is conducted the research in two cycles. The research findings showed that the mean score of students’ reading comprehension in the first cycle is 69 to 88 in the second cycle which means it successffully passed the KKM. It can be concluded that the students’ reading comprehension especially in getting main idea, supporting detail and vocabulary aspect taught by semantic mapping was improved. Keywords: Reading Comprehension, Descriptive Text, Semantic Mapping Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan siswa dalam pemahaman membaca. Penelitian ini telah dilakukan terhadap siswa kelas X TAV SMK PGRI Pontianak pada tahun akademik 2014/2015. Dalam penelitian ini sasaran penelitiannya adalah siswa kelas X TAV yang terdiri dari 20 orang siswa. Penelitian ini menggunakan metode penelitian tindakan kelas dan berperan sebagai guru selama masa penelitia berlangsung. Data dikumpulkan menggunakan tehnik penilaian dan observasi langsung dengan menggunakan tabel pemeriksaan, catatan lapangan, dan tes. Tehnik yang digunakan adalah semantic mapping dan dilaksanakan dalam 2 siklus. Hasil penelitian menunjukan skor rata-rata tes siswa pada siklus pertama adalah 69 menjadi 88 pada siklus kedua yang berarti siswa dapat melewati standar KKM. Berdasarkan hasil tersebut, dapat disimpulkan bahwa pemahaman siswa terhadap membaca, khususnya pada ide utama, kalimat pendukung dan kosakata dapat meningkat melalui pengajaran menggunakan semantic mapping.   Keywords: Pemahaman Membaca, Teks Deskripsi, Pemetaan Semantik